Enhancing Da'wah Professionalism and Competence of Amil Zakat (Zakat Manager) in Indonesia - Choirin, Muhammad; Sudrajat, Achmad; Sarniti, Sarniti; Khareng, Mutsalim (Jurnal Dakwah Risalah, 2024)
The effective management of zakat institutions depends significantly on the competence of amil zakat and their alignment with da'wah professionalism to fulfill religious and operational expectations. This study investigates the role of the Pusdiklat (Training and Education Center) and the LSP (Professional Certification Institution) in advancing da'wah professionalism and enhancing the competence of amil zakat in Indonesia. This paper adopts a qualitative approach. The research gathered data through in-depth interviews and document analysis from multiple zakat institutions partnered with Pusdiklat and LSP. Findings indicate that Pusdiklat's training programs have significantly improved amil zakat knowledge, skills, and attitudes while strengthening essential aspects of da'wah professionalism. Meanwhile, certification provided by LSP has facilitated the assessment and recognition of amil zakat professional competence, bolstered public trust in zakat institutions, and improved operational efficiency. However, challenges such as financial limitations, limited awareness about the importance of certification, and the need for enhanced collaboration among Pusdiklat, LSP, and zakat institutions were identified. In conclusion, this study finds that bolstering the competence of amil zakat through LSP holds substantial potential to elevate the performance and professionalism of zakat institutions in Indonesia.